A comparative, prospective and randomized evaluation of roux-en-y gastric bypass with and without the silastic ring: a 2-year follow up preliminary report on weight loss and quality of life - Rasera, I. [UNESP]; Coelho, T. H.; Ravelli, M. N.; Oliveira, M. R. M.; Leite, C. V. S.; Naresse, L. E.; Henry, M. A. C. A. (Springer, 2015)
Currently, Roux-en-Y gastric bypass (RYGB) is one of the most widely used bariatric surgeries. Banding the pouch forms a banded gastric bypass operation, an accepted and frequently used variant. Placing a silastic ring around the pouch to band the gastric bypass operation increases the restriction mechanism. However, the ubiquitous use of the banded gastric bypass remains controversial. One of the controversies is the effect of the silastic ring on patients' perception of their well being after surgery because of the frequency of vomiting. A prospective, blindly randomized, comparative trial was undertaken to resolve this controversy. Four hundred subjects scheduled for gastric bypass surgery were randomized into two arms of the trial, 200 with a silastic ring (WR) and 200 without (NR). After 2-year follow-up, the variables associated with the scores of Bariatric Analysis and Reporting Outcome System (BAROS) were analyzed. The initial median weight (125 kg), BMI (47), and age (36 years) were the same in both the NR and WR groups. The median excess weight loss, weight regain, and incidence of vomiting were 71, 10.5, and 7.75 %, respectively, in the NR group vs. 75.4 and 1.1, and 24.4 % in the WR group. The mean QOL score was 79 % in the NR group vs. 80 % in the WR group. After 2-year follow-up, silastic ring placement in the RYGB resulted in greater weight loss and weight stability and a threefold greater incidence of vomiting. There was no difference in the scores in the quality of life analysis.
Keywords: Morbid obesity; Gastric bypass; Bariatric surgery; Weight loss; Silastic ring; Postoperative complications; Quality of life